2010
DOI: 10.1182/blood-2009-08-239681
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel cluster groups in pediatric high-risk B-precursor acute lymphoblastic leukemia with gene expression profiling: correlation with genome-wide DNA copy number alterations, clinical characteristics, and outcome

Abstract: To resolve the genetic heterogeneity within pediatric high-risk B-precursor acute lymphoblastic leukemia (ALL), a clinically defined poor-risk group with few known recurring cytogenetic abnormalities, we performed gene expression profiling in a cohort of 207 uniformly treated children with high-risk ALL. Expression profiles were correlated with genome-wide DNA copy number abnormalities and clinical and outcome features. Unsupervised clustering of gene expression profiling data revealed 8 unique cluster groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
376
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(404 citation statements)
references
References 35 publications
24
376
2
2
Order By: Relevance
“…34 Furthermore, while concluding the current report, a study was published analyzing the genetic basis for relapse in 207 uniformly treated children with high-risk preB-ALL. 35 This study revealed eight unique genetic clusters within high-risk ALL patients, of which the expression of Fat1 was highly ranked (59th) within cluster R2, a cluster also associated with the t(1;19)(E2A-PBX1) translocation; however, we found that Fat1 within this cohort was not prognostic on its own for overall survival (data not shown). This does not contradict the work presented in the current manuscript where Fat1 expression was found to be an independent prognostic marker in paired diagnosis-relapse patients, but yields important information behind the biology of relapse, information that continues to be needed to successfully cure the patients whom relapse.…”
Section: Discussionmentioning
confidence: 62%
“…34 Furthermore, while concluding the current report, a study was published analyzing the genetic basis for relapse in 207 uniformly treated children with high-risk preB-ALL. 35 This study revealed eight unique genetic clusters within high-risk ALL patients, of which the expression of Fat1 was highly ranked (59th) within cluster R2, a cluster also associated with the t(1;19)(E2A-PBX1) translocation; however, we found that Fat1 within this cohort was not prognostic on its own for overall survival (data not shown). This does not contradict the work presented in the current manuscript where Fat1 expression was found to be an independent prognostic marker in paired diagnosis-relapse patients, but yields important information behind the biology of relapse, information that continues to be needed to successfully cure the patients whom relapse.…”
Section: Discussionmentioning
confidence: 62%
“…In line with this observation, multiple deletions in lymphoid development genes are frequently observed in Ph-like patients. 22,23,25 IKZF1 deletions were identified as an independent prognostic factor for CIR in the whole series but not in the Ph-negative subgroup. The low number of Phpositive patients does not allow specific conclusions to be drawn regarding the prognosis.…”
Section: Discussionmentioning
confidence: 77%
“…EBF1 losses were enriched in the ETV6-RUNX1 subtype (the most common cytogenetic aberration in childhood B-cell ALL), although this is rarely observed in adult Bcell ALL. 4 Harvey et al 22 showed that EBF1 deletions were present in only the 2 poorest outcome groups in a series of 207 children with high-risk ALL, and they correlated with the BCR-ABL1-like signature. Den Boer et al 23 showed that EBF1 deletions were exclusively present in the BCR-ABL1-like subtype and were associated with resistance to L-asparaginase and daunorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 In addition, there are case reports of patients responding to TKI treatment indicating that these aberrations represent a promising and relevant therapeutic target especially given the reported unfavorable prognosis of BCR-ABL1-like ALL. [5][6][7][11][12][13][14] However, the biology of this heterogeneous group of abnormalities is not fully understood and there is evidence that the prognosis of patients depends on the type of kinase activating lesion and the presence of cooperating aberrations such as IKZF1 deletions and JAK2 mutations. 7 Further studies, based on patients with specific gene fusions, are therefore warranted.…”
Section: Introductionmentioning
confidence: 99%